Moral Message Of Nature's Sustainability: Semiotic Analysis Of Alam Menyapa On Audio-Visual Music Composition - Junita Batubara; Emmi Simangunsong; Kamaluddin Sigalingging; Ance Juliet Panggabean (Gondang: Jurnal Seni dan Budaya, 2022)
Alam Menyapa is a musical composition which is a blend of Western and traditional music from various countries. The idea for Alam Menyapa came from the composition Song of the Birds, which was once used as therapeutic music for drug-affected patients, at the Mutiara Abadi Foundation in Binjai City. One of the uniqueness of Alam Menyapa is the adoption of natural sounds, such as the sounds of various birds, the sound of river water, the sound of wind blowing, and other animal sounds, which are then digitally combined with various musical instruments. The method used is descriptive qualitative, collecting data with literature, observation, interviews and documentation. The data analysis technique used is interactive analysis from Milles and Hubermann. The results of this study indicate that Alam Menyapa has a simple musical concept which includes: 1) The musical instruments used are a blend of Western and traditional music through digital music, 2) Musical elements; playing rhythmic patterns that complement each other, simple melodies with simple dynamic signs 3) Forms of presentation through recordings of natural sounds included in digital music and audio-visual. 4) The symbolic meaning of balanced natural life, 5) The aesthetic expression of harmony and simple chords, and 6) The educational value contained is that the sounds of nature can be applied to digital music with simple melodies and harmonies. The theory of meaning or symbols used by the author in conducting research is the theory of Roland Barthes. The result of the research is an analysis of Indonesian music composition with the aim that more and more works by Indonesian composers will be introduced to the world through analysis.